Impact properties of the aircraft cast aluminium alloy Al-7Si0.6Mg (A357) - Alexopoulos N.D. (EPJ Web of Conferences, 2010)
The impact mechanical properties of the widely used in the aeronautics A357 cast aluminum alloy were investigated by exploiting experiments on an instrumented Charpy impact testing machine. The evaluated impact properties for 25 different artificial aging heat treatment conditions were analyzed and discussed in conjunction with the respective tensile properties. Correlations are proposed to establish useful relationships between impact resistance and tensile strain energy density properties. The established correlations, which are well supported by the performed experiments, can be used to estimate the tensile ductility and toughness of the A357 cast aluminum alloy from the Charpy impact test. Performed fractographic analyses were supporting the physically arbitrary correlation between tensile strain energy density and impact resistance.